What if becoming information literate were an adventure? - Dahl, Tove I. (Nordic Journal of Information Literacy in Higher Education, 2022)
What if becoming information literate were an adventure? This question was posed in a keynote for the Creating Knowledge Conference 2021. It was answered in a thought piece by examining adventure-based ways to prepare students to be information literate adults through the principles and mechanisms that people find arousing and pleasurable and that are not classically a part of university pedagogy. How might these mechanisms be used to engage students more in the IL learning process and to encourage them to pursue being an information literate person as a lifelong endeavor? Adventure is presented as an experience that is situated, soft or hard, emotionally charged, challenging and rewarding. The risk aspect of adventure, often linked to danger, is also examined. Some of the dangers that exist in the management of information are explored (e.g., traps in sharing practices, seductive novelty and bypassing reason) as well as the personal costs of not managing information literacy well. How we nevertheless find danger alluring is explained in terms of arousal, as well as how we navigate zones of danger and delight with the help of protective frames. In order to arouse and sustain student engagement in becoming information literate adults, the value of interest is also introduced with the four-phase model of interest development. Suggestions for where to get started in translating the mechanisms of adventure, danger and interest into theoretically motivated and enjoyable teaching in order to support student growth as lifelong information literate adults are woven into the text for reflection.